Novel Axially Unfixed Biaryl-Based Water-Compatible Organocatalysts: Design, Synthesis and Their Asymmetric Catalysis in Direct Aldol Reactions in Water - Zhao, Hong-Wu; Yue, Yuan-Yuan; Li, Hai-Long; Song, Xiu-Qing; Sheng, Zhi-Hui; Yang, Zhao; Meng, Wei; Yang, Ze (Synlett, 2013)
A family of novel axially unfixed biaryl-based, water-compatible bifunctional organocatalysts were designed and synthesized for asymmetric catalytic direct aldol reactions in water. These organocatalysts are comprised of prolinamide, aromatic sulfonamide and biaryl motifs. Under the optimal reaction conditions, one organocatalyst in particular delivered excellent stereocontrol (up to 99% ee and 99:1 dr) in direct aldol reactions of cyclohexanone with a variety of aromatic aldehydes in water.
Keywords: axially unfixed biaryl; water; organocatalysts; aldol reaction; stereoselectivity